Characterisation of Cape Town brown haze - Walton, Nicola Maria (My University, 2006)
The Cape Town brown haze is a brown-coloured smog that is present over the Cape Town atmosphere during the winter months due to the accumulation of gaseous and particulate pollutants. The main aim of this research was to evaluate the impact of atmospheric pollutants to visibility impairment by the brown haze through visibility modelling of major pollution sources around the City of Cape Town. The screening model, VISCREEN, the Plume Visibility model, PLUVUE II and the CALPUFF Modelling System were employed to model the visual impact of emissions from the major sources. Two point sources, Caltex Oil Refinery and Consol Glass, and three area sources, Cape Town Central Business District (CBD), Cape Town International Airport and the townships of Khayelitsha and Mitchell’s Plain were identified as the major sources. An initial screening analysis indicated that emissions from the two industrial sources would be visible and would result in a yellow-brown discolouration of the atmosphere. Detailed modelling using PLUVUE II identified the area sources of Cape Town CBD and the townships to be the significant contributors to visibility impairment over Cape Town. Plume perceptibility is primarily dependant upon particulate emissions while NOx emissions influence the colouration of the atmosphere. CALPUFF was employed to assess the distribution of NOx, SO2 and PM10 concentrations over the area and the associated visibility impairment on a nonhaze (13 August 2003) and haze day (22 August 2003). Pollutant concentrations were considerably reduced on the non-haze day compared to the haze day. The Cape Town CBD was an important source of all the major pollutants with the townships contributing significantly to the aerosol loading over Cape Town. Pollutant concentrations are particularly elevated during the late evening and early morning periods, particularly between 7 am and 8 am. Visibility impairment is greatest on the haze day, particularly over the central Cape Town region and the townships. The greatest reduction in visibility is experienced between midnight and 9 am which corresponds with the periods of elevated atmospheric pollutant concentrations.
Faculty of Science School of Geography And Archaeology and Enviromental Studies 9905693x Nicola@crg.bpb.wits.ac.za
Keywords: Cape Town; Brown Haze; Visibility impairment; Air pollution